Sustainable Materials in the Tire Industry: A Cross-Continental Comparative Study of Europe and Asian Markets - Antony, Albin (Digital Repository of Theses, 2024)
As the global tire industry confronts the pressing need for sustainability, the researcher conducts a comparative analysis of how sustainable materials are being adopted and implemented in the tire manufacturing sector, specifically focusing on the Asian and European markets. This thesis aims to shed light on disparities, trends, and the driving factors behind the integration of sustainable materials in these major automotive and tire markets. To start off, the researcher provides an overview of the challenges faced by the tire industry. The researcher emphasizes the tire industry's substantial contributions to resource depletion and carbon emissions, highlighting the urgency of transitioning towards more sustainable manufacturing practices and sustainable material usage. Furthermore, the study explores how both the Asian and European markets are responding to this need. This research meticulously examines the materials used in tire production, such as alternatives to synthetic polymers, recycled materials, innovative composites, rubber fillers, and other materials like plasticizers, and evaluates how the use of sustainable materials varies across both regions. A central aspect of this thesis involves a comparative analysis of the economic and technical feasibility of adopting sustainable materials in the tire industry, accounting for the diverse market dynamics, regulations, and consumer preferences in Asia and Europe. The study also investigates the challenges and opportunities that manufacturers encounter as they seek to transition to more sustainable material usage. To substantiate the comparative findings, the thesis incorporates interviews and surveys of tire and raw material manufacturers and end users from Asian as well as European markets, illustrating successful strategies and innovative approaches. These case studies offer practical insights and potential pathways for manufacturers aiming to align their practices with sustainability goals. In conclusion, this research underscores the importance of regional variations in the adoption of sustainable materials within the tire industry, recognizing that cultural, economic, and regulatory factors influence the rate of transformation. The findings of this study emphasize that while there are common goals in the Asian and European tire markets to adopt sustainable materials and practices, unique challenges and opportunities exist in each region. Ultimately, this thesis encourages a collective effort towards more sustainable tire material usage and manufacturing practices, promoting the greener future of the global tire industry.